Socio-Economic Challenges of Parents of Children with Intellectual Disability: A Community-Based Study in Lagos, Nigeria - Manuel, Nkechi Mojisola; Thomas, Ifueko Omowunmi; James, Vera Emiokpa; Eke, Vitalis Ugochukwu (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
This study investigated the challenges facing parents of children with Intellectual disabilities (ID) in Lagos, Nigeria. The study adopted a descriptive research design with a purposive sampling technique to select available thirty (30) parents of children with ID drawn from the Association for Intellectual and Developmental Disabilities of Nigeria as the study sample. Four research questions were raised to guide the study. A validated self-designed questionnaire titled 'Questionnaire on Challenges Facing Parents of Children with ID (QCFPCID r=067)' was used for data collection. Data were analyzed using mean, frequency count, and simple percentages. Results revealed that family members with ID negatively affect the family economy, family living standard, and all children's education. Based on the findings of the study, it was recommended that government should make provisions for social welfare that will help reduce the challenges facing parents of children with ID.